A history of childhood trauma and allostatic load in patients with psychotic disorders with respect to stress coping strategies. (May 2020) - Piotrowski, Patryk; Frydecka, Dorota; Kotowicz, Kamila; Stańczykiewicz, Bartłomiej; Samochowiec, Jerzy; Szczygieł, Krzysztof; Misiak, Błażej
Highlights: The allostatic load index was significantly higher in patients with psychosis. Parental antipathy was related to higher allosatic load in patients with psychosis and controls. Sexual abuse might contribute to allosatic load in patients with psychosis but not in controls. Social interactions in case of stress might suppress the association between sexual abuse and allostatic load in psychosis. Abstract: Elevated allostatic load (AL) index, which is a cumulative measure of biological dysregulations associated with stress exposure, has been demonstrated in patients with psychosis. However, it remains unknown whether a history of childhood trauma (CT) might contribute to elevated AL index in psychosis. Therefore, we aimed to investigate the association between AL index, a history of CT and coping styles in patients with psychotic disorders. Participants were 65 patients with schizophrenia-spectrum disorders and 56 healthy controls (HCs). The AL index was computed based on percentile distributions of 15 biomarkers in HCs. The AL index was significantly higher in patients with psychosis. A history of parental antipathy was associated with elevated AL index in both groups of participants. A history of any categories of CT and sexual abuse were associated with higher AL index only in patients with psychosis. Social diversion (seeking social interactions in case of stressful experiences) mediated the association between sexual abuse and the AL index in the group of patients. There was a significant direct effect of sexual abuse on the AL index (this specific CT was associated with higher AL index). However, indirect effect of sexual trauma on AL through social diversion was opposite to direct effect. Childhood adversities, especially sexual abuse and parental antipathy, might contribute to elevated AL index in patients with psychosis. The effect of sexual abuse on the AL index might be specific to psychosis. Engagement in social interactions in case of stressful situations might alleviate biological dysregulations associated with CT.